AICA RIBOSIDE ANALOGS FOR TREATMENT OF ACUTE DECOMPENSATED HEART FAILURE - Richard R. STOVER (2018)
The present disclosure provides methods and compositions for treating acute heart failure, by administering to a subject in need thereof a therapeutically effective amount of an AICA riboside analog or a pharmaceutically acceptable salt or prodrug thereof.